Neutrophil-to-Lymphocyte Ratio as a Prognostic Marker in Infective Endocarditis: In-Hospital and Long-Term Clinical Results - (:unkn) unknown (I C R PUBLISHERS, 2014)
Background and aim of the study: The neutrophil-to-lymphocyte ratio (NLR) is an independent predictor of poor prognosis in different clinical conditions such as infectious and cardiovascular diseases. It was hypothesized that a patient's admission NLR would be predictive of an adverse clinical outcome in cases of infective endocarditis (IE). Methods: A total of 171 patients with IE was enrolled retrospectively, and allocated to two tertiles based on admission NLR values. The high-NLR group (n = 76) was defined as having an NLR value in the third tertile (>5.46), and the low-NLR group (n = 95) as having a value in the lower two tertiles (<= 5.46). Results: Patients in the high-NLR group had a significantly higher incidence of in-hospital mortality than the low-NLR group (39.4% versus 18.9%, p = 0.003). A high NLR was found to be an independent predictor of in-hospital mortality (odds ratio 2.53, 95% confidence interval 1.19-5.3; p = 0.01). The mean follow up was 25.5 months, and long-term follow up mortality was similar in both groups (12.9% versus 19.5%; p = 0.33). Conclusion: A high NLR at admission is associated with increased in-hospital mortality in patients with IE. During the long-term follow up, NLR showed no predictive indication of mortality.
Keywords: DENSITY-LIPOPROTEIN CHOLESTEROL; ELEVATION MYOCARDIAL-INFARCTION; C-REACTIVE PROTEIN; PREDICTIVE-VALUE; SEPTIC SHOCK; APOPTOSIS; DIAGNOSIS; SEPSIS; LYMPHOPENIA; BACTEREMIA